Levels of the Enterolobium cyclocarpum pod in feedlot diet on growth performance, ruminal fermentation and biogas production of lambs-hair - LÓPEZ-GARRIDO, SERAFÍN J; SALAZAR-MENDOZA, ALDO A; GALICIA-JIMENEZ, MÓNICA M; CAMACHO-ESCOBAR, MARCO A; ÁVILA-SERRANO, NARCISO Y; RAMÍREZ-BRIBIESCA, J EFRÉN (The Indian Journal of Animal Sciences, 2020)
Enterolobium cyclocarpum (Ec) is a native legume that grows from southern Mexico to South America; its seeds are traditionally used for feeding ruminants. The objective of this study was to evaluate the addition of Ec pods in diets of hair lambs and their effect on the productive variables, ruminal fermentation and in vitro production of methane (CH4) and carbon dioxide. Thirty male lambs fed diets containing 0% (Ec0), 20% (Ec20) and 40% (Ec40) based on dry matter were evaluated. The addition of Ec40 in the integral diet of the lambs did not affect the growth performance. The pH of the ruminal fluid did not show differences between the treatments. The addition of Ec40 increased propionate and decreased acetate. Protozoa decreased in 47 and 59% with Ec20 and Ec40, respectively; while the population of cellulolytic bacteria decreased with Ec40. In vitro degradability of dry matter was lower in 8.8% with the inclusion of Ec40 in diets. The novelty of the study was that Ec40 diet decreased the ruminal methane production.